2015
DOI: 10.3109/09638288.2015.1061609
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life improvements among women with chronic pain: comparison of two multidisciplinary interventions

Abstract: Chronic pain is a debilitating condition affecting quality of life and restricting societal participation. Intensive multidisciplinary bio-psycho-social rehabilitation is essential for this patient group. This study shows improvement in health-related quality of life and pain intensity following such rehabilitation. Emphasizing mindfulness based cognitive therapy and neuroscience patient education improves sleep to more extend than more traditional approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…The “Living Healthy” program, adapted from the Pakistani CBT‐based intervention delivered by Lady Health Workers and designed to prevent postpartum depression, is one of the first interventions that combined peer support and CBT for managing chronic pain in adults with diabetes. Both peer support 43 and CBT 16 have been previously shown to be effective in the treatment of chronic pain 44,45 or diabetes 22,23,46 separately, but not concurrently. For example, Moore et al conducted a CBT‐based psychologist‐led intervention for primary care patients with chronic back pain 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The “Living Healthy” program, adapted from the Pakistani CBT‐based intervention delivered by Lady Health Workers and designed to prevent postpartum depression, is one of the first interventions that combined peer support and CBT for managing chronic pain in adults with diabetes. Both peer support 43 and CBT 16 have been previously shown to be effective in the treatment of chronic pain 44,45 or diabetes 22,23,46 separately, but not concurrently. For example, Moore et al conducted a CBT‐based psychologist‐led intervention for primary care patients with chronic back pain 20 .…”
Section: Discussionmentioning
confidence: 99%
“…One study reported that anxiety, depression, and severe impairment were prevalent within this population [14], and it has been shown that patients with pain of high intensity as well as persistent pain have lower HRQoL [15,16]. Additionally, several studies evaluated the impact of an intervention on HRQoL in those with pain [17,18,19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Women with chronic pain who participated in a rehabilitation program that offered either traditional multidisciplinary pain management or neuroscience education and mindfulness-based cognitive therapy were studied. The results indicate that both programs improved quality of life and reduced pain intensity [ 20 ] and that the improvements lasted six months after the program’s completion [ 21 ]. No Icelandic study focusing specifically on the long-term effects of these programs on chronic pain, sleep, and HRQOL was found.…”
Section: Introductionmentioning
confidence: 99%